PENGARUH KINERJA KARYAWAN MARKETING PADA JUMLAH PEMBIAYAAN STUDI KASUS PT. BANK SUMUT KANTOR CABANG SYARIAH MEDAN - Syarifah Aini Tanjung; Kamilah; Nurbaiti (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study aims to assess the correlation between the quantity of funding and the marketing performance of employees (studi kasus PT. Bank Sumut Kantor Cabang Syariah Medan). The research methodology used is an analytical descriptive approach. This approach focuses research on the performance of the marketing employee as well as any variable that serves as a performance measure. The parties responsible for the performance of the marketing staff at the Shariah Branch Office of Sumut Bank were selected as the subject of this study. This research uses primary and secondary data. The interview that he did with a marketing employee of P.T. Bank Sumut Shariah Field Branch Office was a research instrument he used. This study uses qualitative descriptive analysis as its method of data collecting. It is a recording procedure used to describe or depict the state of an object being studied based on the fact that it exists. Data collection techniques used include observations, interviews, documentation, and libraries.